Posture as Index for Approach-Avoidance Behavior - Eerland, Anita; Guadalupe, Tulio M.; Franken, Ingmar H. A.; Zwaan, Rolf A. (PLOS ONE, 2012)
Approach and avoidance are two behavioral responses that make people tend to approach positive and avoid negative situations. This study examines whether postural behavior is influenced by the affective state of pictures. While standing on the Wii™ Balance Board, participants viewed pleasant, neutral, and unpleasant pictures (passively viewing phase). Then they had to move their body to the left or the right (lateral movement phase) to make the next picture appear. We recorded movements in the anterior-posterior direction to examine approach and avoidant behavior. During passively viewing, people approached pleasant pictures. They avoided unpleasant ones while they made a lateral movement. These findings provide support for the idea that we tend to approach positive and avoid negative situations.